2015
DOI: 10.1371/journal.pone.0125162
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Bacterial-Derived DNA Fragment Level Is a Strong Predictor of Cardiovascular Disease in Peritoneal Dialysis Patients

Abstract: BackgroundCirculating bacterial DNA fragment is related to systemic inflammatory state in peritoneal dialysis (PD) patients. We hypothesize that plasma bacterial DNA level predicts cardiovascular events in new PD patients.MethodsWe measured plasma bacterial DNA level in 191 new PD patients, who were then followed for at least a year for the development of cardiovascular event, hospitalization, and patient survival.ResultsThe average age was 59.3 ± 11.8 years; plasma bacterial DNA level 34.9 ± 1.5 cycles; avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…It should be noted, however, that our local policy mandates hospital admission for many intervention procedures, such as cardiac catheterization and colonoscopy. Unfortunately, we do not have the detailed breakdown on the cause of hospitalization for our patients, but the gure in this study is similar to our previous reports [29,30].…”
Section: Discussionsupporting
confidence: 80%
“…It should be noted, however, that our local policy mandates hospital admission for many intervention procedures, such as cardiac catheterization and colonoscopy. Unfortunately, we do not have the detailed breakdown on the cause of hospitalization for our patients, but the gure in this study is similar to our previous reports [29,30].…”
Section: Discussionsupporting
confidence: 80%
“…Based on our studies, both plasma mitochondrial and bacterial DNA levels correlate with serum CRP level and predict cardiovascular events [14,17], but the plasma levels of the two DNA species have no internal correlation (our unpublished data). It could be argued that since the PCR cycle number of plasma mitochondrial DNA level is generally around 15 lower than bacterial DNA level, the absolute level of the former is at least 1000-fold higher than the latter.…”
Section: Discussionmentioning
confidence: 82%
“…Mitochondrial DNA is structurally similar to bacterial DNA and contains unmethylated CpG motifs that binds to toll-like receptor-9 (TLR-9) [18][19][20][21][22], which results in downstream activation of an inflammatory cascade and potentially acute cardiac damage [27,28]. Our previous studies showed that plasma level of bacterial DNA fragment, which activates the same TLR-9 pathway, correlates with the severity of systemic inflammation and is a strong predictor of cardiovascular event, need of hospitalization, as well as the progressive change in arterial stiffness in new PD patients [14,17]. Taken together, these studies suggest that both endogenous (mitochondrial) and exogenous (bacterial) DNA fragments are important uremic toxins that contribute to the pathogenesis of systemic inflammation and cardiovascular disease in PD and probably CKD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…68 In another study on patients on PD, plasma endotoxin level correlated with the number of hospital admission and duration of hospitalization for cardiovascular reasons. 69 In patients on hemodialysis, a cohort study found that plasma endotoxin level had a modest but significant correlation with serum CRP level and is an independent predictor of patient death within 3 years. 70 In another study, plasma endotoxin level significantly correlated with serum soluble CD14 level, which is associated with inflammation and protein-energy wasting.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%